D-Amphetamine Accelerates Recovery of Consciousness and Respiratory Drive After High-Dose Fentanyl in Rats - Moody, Olivia A.; Zhang, Edlyn R.; Arora, Vipin; Kato, Risako; Cotten, Joseph F.; Solt, Ken (Frontiers in Pharmacology, 2020)
In the United States, fentanyl causes approximately 60,000 drug overdose deaths each year. Fentanyl is also frequently administered as an analgesic in the perioperative setting, where respiratory depression remains a common clinical problem. Naloxone is an efficacious opioid antagonist, but it possesses a short half-life and undesirable side effects. This study was conducted to test the hypothesis that d-amphetamine ameliorates respiratory depression and hastens the return of consciousness following high-dose fentanyl. Behavioral endpoints (first head movement, two paws down, and return of righting), arterial blood gas analysis and local field potential recordings from the prefrontal cortex were conducted in adult rats after intravenous administration of fentanyl (55 µg/kg) at a dose sufficient to induce loss of righting and respiratory depression, followed by intravenous d-amphetamine (3 mg/kg) or saline (vehicle). D-amphetamine accelerated the time to return of righting by 36.6% compared to saline controls. D-amphetamine also hastened recovery of arterial pH, partial pressure of CO2 and O2 and of sO2 compared to controls, with statistically significant differences in pH after 5 minutes and after 15 minutes. Local field potential recordings from the prefrontal cortex showed that within 5 minutes of d-amphetamine administration, the elevated broadband power <20 Hz produced by fentanyl had returned to awake baseline levels, consistent with the return of consciousness. Overall, d-amphetamine attenuated respiratory acidosis, increased arterial oxygenation, and accelerated the return of consciousness in the setting of fentanyl intoxication. This suggests that d-amphetamine may be a useful adjunct or alternative to opioid receptor antagonists such as naloxone.